Road salt inputs alter biogeochemistry but not plant community composition in exurban forested wetlands - Samantha E. Walker (Wiley, 2021)
Abstract Forested wetlands of the temperate north are increasingly exposed to deicing salts, but it is unclear how this may alter wetland biogeochemistry and plant community composition. To investigate potential effects of deicing salts on exurban forested wetlands in southern New England, we employed a multi‐site field study to describe spatiotemporal patterns of soil physiochemical, water quality, and vegetation characteristics with distance from road deicing salt source. We surveyed nine road‐adjacent, red maple‐dominated wetlands to quantify a suite of soil parameters (Na+, K+, Mg2+, Ca2+, pH, electrical conductivity (EC), heavy metals, N, P, and soil moisture), as well as surface and groundwater salinity, and vegetation communities. With increasing distance from roads along 165‐m transects penetrating into each wetland, soil salinity (EC, Na+) decreased, while soil base cation concentrations (Mg2+, Ca2+) increased, likely due to cation exchange (Na+ displacing other base cations). We also measured foliar chemistry and observed elevated Na+ and reduced Mg2+ of dominant species leaf tissue near roads, suggesting plant nutrient uptake responds to road salt‐related changes in soil physicochemical variables. Despite this, we did not detect differences in plant community composition (ground, shrub layers) along road salt‐induced soil chemistry gradients in the field, likely because surface and groundwater salinities were relatively low (maximum: 0.64 ppt). To determine at which field salinities we could potentially expect changes in wetland plant communities, we conducted a full‐factorial, manipulative seed bank experiment to examine how NaCl concentrations (0, 0.5, 1, 2, 4, and 8 parts per thousand (ppt)), frequency of salt exposure (pulse, constant), and water level (surface, 2 cm below surface) affected soil seed bank responses. Seedling richness was reduced at salinities exceeding 1 ppt, and seedling density was reduced above 2 ppt, but pulsing tended to alleviate salt‐induced reductions in seed bank responses. As salinization of freshwater ecosystems continues to increase, our results suggest that field salinity levels of exurban New England forested wetlands are nearing yet still typically below the threshold for which we expect to see strong plant community responses.